Projeto e construção de um conversor monofásico em ponte H multicelular entrelaçado para geração fotovoltaica e eólica de pequeno porte - Geovane Luciano dos Reis (2017)
The demand for electricity has been increased in recent years, in addition to that, the search for new sources of energy to meet this growth in nonpolluting and sustainable way. Thus, renewable energies sources such photovoltaic and wind power has been gaining prominent position in the world energy scenario. The purpose of this work is to present the design, construction and commissioning of a single-phase hybrid H-bridge parallel multicell converter for photovoltaic and small wind generation, with nominal power of 11.7kW. The system consists of i) two photovoltaic arrays of 5.1kW each one, that have their maximum power point tracked by two interleaved Boost converters ii) a wind turbine with permanent magnet synchronous generator with nominal power of 1.5kW, whose the maximum power point is tracked by a third boost converter. The interface between the power generation system and the electrical grid is carried out by a four arms interleaved voltage source inverter, connected to ICT inductor. The present theses show the main concepts of photovoltaic and wind power generation, components modelling, used control techniques and systems maximum power point tracking. Finally, the simulated and experimental results for the developed system are present and discussed